Leeway Space Mandibula pada Siswa Suku Minang di Sekolah Dasar Lubuk Sikaping, Sumatera Barat - Ayu Shafira; Hafni Bachtiar; Didin K (Andalas Dental Journal, 2018)
The prediction of permanent size of theet which haven’t errupted to determine the value of place needed, availability of space and predict the storage of space. Is one of important aspect in diagnosis and treatment planning on the period of mixed dentition. Prediction method that used commonly is Moyers method which the data is taken from Kaukasoid ras. The objective of the research is to see the difference of leeway space of mandibula on Minang man and woman students of elemantary school Lubuk Sikaping. The method of this research is cross sectional comprative study. 56 samples of mandibula study are taken from the student of SDN 06 Pauh, SDN 09 Pauh, and SDN 10 Pauh Lubuk Sikaping at the age of 8 to 10 years and they are Minangnese. The results are analyzed statistically by t-test on significant degree 95%. This research indicates that the large average of man mandibula leeway space on the left (1,76 mm) and on the right (1,85 mm). And the average of leeway space of woman mandibula leeway space on the left (2,03 mm) and on the right (2,16 mm). The analyze t-test result on the significant degree 95% show there is no significant difference (p>0,05) between man and woman students. Therefore, it can be concluded that the large average of leeway space of man and woman mandibula in Minang students of elementary school Lubuk Sikaping showed no significant difference in size.